Comparison of the Effectiveness of Leaflet and Educational Video Media on the Improvement of Antibiotic Knowledge in Simpang Empat Sungai Baru Village - Nafisa, Sherin; Kurniawati, Darini; Alawiyah, Tuti; Mustaqimah, Mustaqimah (International Journal of Education, Information Technology, and Others, 2023)
The phenomenon of residents of Simpang Empat Sungai Baru Village with the habit of buying antibiotics at unlicensed stalls and drugstores is still rife. Free use of antibiotics is influenced by several factors, one of which is knowledge. One effort that can be done to increase knowledge is to provide effective education. The selected education is to use leaflets and video media. Knowing the comparison of the effectiveness of leaflet and video media on increasing antibiotic knowledge in Simpang Empat Sungai Baru Village. True experimental research with pretest-posttest control group design. The sampling technique used is purposive sampling. The research sample is 96 respondents. The research instrument used a questionnaire. Data analysis used the Wlicoxon Sign Rank test and the Mann Whitney test. Leaflet and video media are effective in increasing people's knowledge about antibiotics with spss analysis the Wilcoxon test results show a Sig. 0.000 which means a significant effect. However, for a comparison of the effectiveness of leaflet and video media, there was no significant effect obtained from the Mann Whitney test results showing the Sig. 0.207. Leaflet and video media were both effective in increasing antibiotic knowledge in Simpang Empat Sungai Baru Village.